Miocene To Quaternary Tectonostratigraphic Evolution Of The Middle Section Of The Burdur-Fethiye Shear Zone, South-Western Turkey: Implications For The Wide Inter-Plate Shear Zones - Elitez, Irem; Yaltirak, Cenk (Aperta, 2016)
The Burdur-Fethiye Shear Zone (BFSZ) is a 75- to 90- km wide and 300-km-long transtensional left-lateral shear zone which is located in one of the most tectonically active regions in south-western Turkey. A considerable number of studies suggested contradictory models of the evolution and Neogene stratigraphy of the BFSZ and in most cases, the local river and alluvial fan deposits were mapped together with the lacustrine sediments and assigned a Pliocene age. We present new field data, fault kinematic analyses, and DEM and earthquake data to characterize the tectonic controls and extent of the middle section of the BFSZ including AcIpayam, cameli and Golhisar basins. Our field observations revealed two distinct sedimentary sequences that unconformably overlie the pre-Neogene basement. The first sequence begins with middle-upper Miocene meandering- and braided-river sediments of the Golhisar Formation, which transition upward into lacustrine sediments of the upper Miocene lower Pliocene lbecik Formation. This sequence is overlain by upper Pliocene-lower Quatemary alluvial fan conglomerates, mudstones and claystones of the Dirmil Formation. The basin deposits located in the middle section of the BFSZ consist of lacustrine sediments of a late Miocene lake that likely evaporated due to the Messinian salinity crisis. Fault kinematic analysis and DEM and earthquake data indicate that the middle BFSZ can be characterized as a heterogeneous left-lateral transtensional shear zone rather than a major fault system. Our findings suggest that the middle section of the BFSZ developed under the influence of progressive counter clockwise rotation of south-western Turkey, the Aegean graben system and the Cyprus and Hellenic arcs since the middle Miocene. (C) 2016 Elsevier B.V. All rights reserved.